Experimental and theoretical results on electron emission in collisions between partially dressed ions with He targets - Monti, Juan Manuel (2013)
Experimental and theoretical results for electron emission in 440 keV u−1 Li+ with He targets are presented. Theoretical cross-sections are obtained using extensions of the continuum distorted wave and the continuum distorted wave-eikonal initial state models to the case of dressed projectiles and a four-body classical trajectory Monte-Carlo. The contributions of electron emission from the different aggregates of the collision system are investigated.